Health insurance and medical impoverishment in rural China: Evidence from Guizhou province - Zhang, Yumei; Filipski, Mateusz J.; Chen, Kevin Z. (World Scientific Publishing, 2017)
We analyze the effects of the New Rural Cooperative Medical Scheme (NCMS) on poverty, using micro-level household data from 17 villages in a poor area of China’s Guizhou province. A four-wave panel dataset allows us to follow NCMS through its reforms. First-order impact assessments suggest NCMS helps reduce the poverty rate by up to 3 percentage points, and the poverty gap by up to 15 percentage points. It also reduces the contribution of health expenditures to inequality as measured by Gini coefficient. The benefits of NCMS in terms of poverty and inequality appear considerably larger after major reforms in 2009, which expanded benefits and coverage.